Unsuccessful attempts to replicate effects of self control operations and glucose on ego-depletion pose an interesting research question that demands explanation - Chatzisarantis, Nikos; Hagger, Martin (Academic Press, 2015)
The hypothesis that sugar-containing drinks counteract depletion of self-control or ego resources is elegant and provocative because it entails that the origins of ego-energy and self-control operations can be traced to a physiological substrate. However, this hypothesis has not withstood scientific scrutiny. Lange and Eggert presented two unsuccessful attempts to replicate effects of glucose on ego-depletion. Chatzisarantis and Hagger argued that inconsistent findings may be due to experimental designs that expose participants to similar acts of self-control. This methodology may not provide a rigorous test of the counteracting effects of glucose on ego-depletion because it does not control for factors (i.e., motivation) that interfere with glucose effects. In this article, we address Lange's comments and explore the possibility that findings reported by Lange and Eggert's and Hagger and Chatzisarantis' studies are consistent. In addition, we discuss a factor that researchers may wish to take into consideration when designing experiments that aim to test effects of glucose, or glucose rinsing, on ego-depletion. This factor is related to ego-depleting value of self-control tasks.